PEMBUATAN MEDIA PENGHARGAAN BERUPA KARTU BINTANG PRESTASI UNTUK MENINGKATKAN MOTIVASI DAN SEMANGAT BELAJAR SISWA - Nanda Sawaku; Asriani Abd. Azis (Journal of Community Services on Multidisciplinary Sciences, 2025)
Low motivation to learn is the main challenge faced by educators in creating effective and meaningful learning. This project aims to increase students' enthusiasm and active participation in the learning process through the use of simple reward media in the form of Achievement Star Cards. This activity is carried out in an elementary school environment involving teachers as the main facilitators and students as recipients of the intervention. The method used is participatory and educational, with the card design as a symbol of appreciation for students' positive behavior and achievements. The results of the activity showed a significant increase in students' activeness, discipline, and enthusiasm for learning. In addition, this project also strengthened the emotional relationship between teachers and students, creating a more supportive and positive classroom climate. With a simple but targeted approach, the star card media has proven to be an effective strategy in managing student motivation.